2011
DOI: 10.1002/tox.20711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trifluralin on the mouse ovary

Abstract: Trifluralin, a herbicide used to protect many arable and horticultural crops, was evaluated for its potential toxicity on the mammalian ovary. To this end, adult female mice were fed or not (control) with a trifluralin-enriched diet (150 mg/kg body weight/day) during gestation and lactation. After weaning, 3-week-old female mice from either trifluralin-treated or control groups were used to evaluate whether the exposure to this herbicide in utero and during lactation could induce stress responses in the ovary.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In vitro, low doses of mancozeb (0.001-1 µg/mL) alter GC morphology [88,117] and mitochondrial metabolism [87]. Similar effects on fertilization have been observed for other sprayed pesticides [118].…”
Section: Air Pollutionsupporting
confidence: 58%
“…In vitro, low doses of mancozeb (0.001-1 µg/mL) alter GC morphology [88,117] and mitochondrial metabolism [87]. Similar effects on fertilization have been observed for other sprayed pesticides [118].…”
Section: Air Pollutionsupporting
confidence: 58%
“…Saghir et al (2008) determined the mechanism of thyroid hyperactivity after TRF exposure and demonstrated that increased levels of TSH and stimulation of thyroid gland would cause cellular hypertrophy, proliferation and development of follicular cell tumours in rats. Cecconi et al (2013) suggested that exposure to a low TRF dose during pregnancy and lactation does not impair oocyte quality, but can induce a stress response in ovarian somatic cells, as TRF causes cytoplasmic degeneration in a slightly higher number of oocytes. Orton et al (2009) used a recombinant yeast screen to detect receptor-mediated (anti-) estrogenic and (anti-) androgenic activity and inhibition of ovulation in vitro , accompanied by decreased testosterone production.…”
Section: Discussionmentioning
confidence: 99%